Human polymorphisms in nicotinic receptors: a functional analysis in iPS‐derived dopaminergic neurons. Issue 2 (17th November 2016) - Deflorio, Cristina; Blanchard, Stíephane; Carisì, Maria Carla; Bohl, Delphine; Maskos, Uwe
ABSTRACT: Tobacco smoking is a public health problem, with ~5 million deaths per year, representing a heavy burden for many countries. No effective therapeutic strategies are currently available for nicotine addiction, and it is therefore crucial to understand the etiological and pathophysiological factors contributing to this addiction. The neuronal a5 nicotinic acetylcholine receptor (nAChR) subunit is critically involved in nicotine dependence. In particular, the human polymorphism a5D398N corresponds to the strongest correlation with nicotine dependence risk found to date in occidental populations, according to meta‐analysis of genome‐wide association studies. To understand the specific contribution of this subunit in the context of nicotine addiction, an efficient screening system for native human nAChRs is needed. We have differentiated human induced pluripotent stem (iPS) cells into midbrain dopaminergic (DA) neurons and obtained a comprehensive characterization of these neurons by quantitative RT‐PCR. The functional properties of nAChRs expressed in these human DA neurons, with or without the polymorphism in the a5 subunit, were studied with the patch‐clamp electrophysiological technique. Our results in human DA neurons carrying the polymorphism in the a5 subunit showed an increase in EC50, indicating that, in the presence of the polymorphism, more nicotine or acetylcholine chloride is necessary to obtain the same effect. This human cell culturing system can now be used in drug discovery approaches to screen for compounds that interact specifically with human native and polymorphic nAChRs.—Deflorio, C., Blanchard, S., Carisì, M.C., Bohl, D., Maskos, U. Human polymorphismsinnicotinic receptors: a functional analysis in iPS‐derived dopaminergic neurons. FASEB J. 31, 828–839 (2017). www.fasebj.org